Vulnerabilidade socioambiental em área peri-urbana suscetível a movimentos de massa: estudo de caso no Distrito de Miritituba, Itaituba, Pará. - SENA, Marson Menezes (Universidade Federal do Pará, 2019)
Natural Disasters associated with mass movements have increased considerably in the last decades, causing a series of physical damages, with consequences mainly on human life, private, public and collective goods. Differently from other regions of Brazil, the Amazon region, despite of the predominance of lowland areas, also suffers from mass movement events caused mainly by the performance of atmospheric rainfall systems that when in excess, produce events of this nature. The objective of this work was to analyze the socioenvironmental consequences of urban occupation in areas of risk of landslides, starting from a case study in the district of Buritizal, District of Miritituba, Itaituba / PA and presenting administrative solutions through elaboration and proposition of a bill in the Itaituba City Council that aims to reserve housing through the National Popular Housing Program for families who have lost their homes or live in areas on the risk of natural disasters. The present study was carried out based on two lines of research, one of bibliographic and the other of field, with mixed approach (quantitative and qualitative), in order to show the problem in the studied context. So, socioeconomic indicators were used from the e-SUS questionnaires, such as, from secondary data obtained from the IBGE, to the municipality of Itaituba and CPRM. The means of social vulnerability were related to the means of environmental vulnerability. From the described scenarios, it was possible to verify that the scenario referring to social variables showed 90% of average vulnerability. On the other hand, the scenario regarding environmental vulnerability was the most critical, with more than 75% of high vulnerability. Summarize, it is verified that both the variables that make the social indicators and the environmental factors have been determinant on the definition of the socio-environmental vulnerability scenario. Socio-environmental vulnerability reached 2.7, so the socioenvironmental vulnerability of families living in the neighborhood of Buritizal was defined as high. The Socio-environmental Vulnerability allowed to observe and quantify the different levels of vulnerability experienced by each family surveyed, and it is possible to indicate which families have more or less vulnerability residing in the neighborhood of Buritizal.